A family of CuI-based 1D polymers showing colorful short-lived TADF and phosphorescence induced by photo- and X-ray irradiation. Issue 13 (7th March 2023) - Artem'ev, Alexander V.; Doronina, Evgeniya P.; Rakhmanova, Mariana I.; Hei, Xiuze; Stass, Dmitri V.; Tarasova, Ol'ga A.; Bagryanskaya, Irina Yu.; Samsonenko, Denis G.; Novikov, Alexander S.; Nedolya, Nina A.; Li, Jing
Abstract : We present 1D CuI-based polymers exhibiting remarkable short-lived TADF and phosphorescence induced by photo- or X-ray irradiation. Abstract : Exploiting 2-(alkylsulfonyl)pyridines as 1, 3-N, S-ligands, herein we have constructed 1D CuI-based coordination polymers (CPs) bearing unprecedented (CuI) n chains and possessing remarkable photophysical properties. At room temperature, these CPs show efficient TADF, phosphorescence or dual emission in the deep-blue to red range with outstandingly short decay times of 0.4–2.0 μs and good quantum performance. Owing to great structural diversity, the CPs demonstrate a variety of emissive mechanisms, spanning from TADF of 1 (M + X)LCT type to 3 CC and 3 (M + X)LCT phosphorescence. Moreover, the designed compounds emit strong X-ray radioluminescence with the quantum efficiency of up to an impressive 55% relative to all-inorganic BGO scintillators. The presented findings push the boundaries in designing TADF and triplet emitters with very short decay times.